Media Sustainability During the COVID-19 Pandemic: Business Differentiation Strategies by Tempo Inti Media Harian - Dadang Rahmat Hidayat; Adinda Afifah Damayanti; Rinda Aunillah Sirait (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
Economic pressures generated by the COVID-19 pandemic were a challenge for Tempo Media Group, especially in the aspect of media business sustainability. The biggest challenge for this media group is faced by Tempo Inti Media Harian, which is forced to accelerate digital transformation. Koran Tempo, which is a printed newspaper, as of 2021 has fully transitioned into Koran Tempo Digital. This change driven by digital disruption is considered necessary to maintain the media business. This article reviews how Tempo Inti Harian's efforts to survive the COVID-19 pandemic from the perspective of Michael Porter's business differentiation strategy. The research used a qualitative method with a descriptive approach. The research was conducted by interacting with and observing the object under study to gain experience to strengthen interpretation and analysis with an inductive approach. The author relates the research findings to the company's ideology in the form of Tempo Cultural Values: Trusted, Independent, and Professional with the basic framework of mass media-McQuaill and the Journalistic Code of Ethics. The results show that in terms of business differentiation strategy, Tempo Inti Media Harian's strength in surviving the COVID-19 pandemic is its consistency in adhering to media accountability and the Journalistic Code of Ethics.